Difference in fascicle behaviors between superficial and deep quadriceps muscles during isometric contractions. Issue 5 (1st March 2016) - Ando, Ryosuke; Nosaka, Kazunori; Inami, Takayuki; Tomita, Aya; Watanabe, Kohei; Blazevich, Anthony J.; Akima, Hiroshi
ABSTRACT: Introduction: In this study we examined changes in fascicle length and pennation of vastus intermedius (VI) and vastus lateralis (VL) from rest to isometric contraction. Methods: Fourteen healthy men performed submaximal (30% and 50% of maximal voluntary contraction; MVC) isometric knee extensions at 60° and 110° knee flexion (0° = full extension). Panoramic images of VL and VI were obtained at rest and during contractions to measure fascicle length and pennation using extended field‐of‐view ultrasonography, after confirmation that the technique could be used reliably during sustained submaximal isometric contractions. Results: The relative change in fascicle length from rest to 50% MVC was greater in VI than VL at 110° ( P < 0.05). Pennation increased during contraction at 60° for VL ( P < 0.05), but not for VI. Conclusion: Muscle‐dependent fascicle behaviors were observed during contraction. These findings may provide a mechanistic underpinning for differences in sarcomere length changes, relative force contribution, and blood flow during contraction. Muscle Nerve 53 : 797–802, 2016